Sebuah - Agnes Yohalina; Efrisca Damanik; Sidarta Sagita; Agnes Yohalina (Universitas Nusa Cendana, 2025)
ABSTRACT Background: Environmental contaminants and hazardous substances are the initiators that cause damage to human organs. DMBA found in motor vehicle pollutants, cigarettes, burning factory fumes can cause liver damage. The liver that is constantly exposed to toxic substances can be damaged. Turmeric with antioxidants and anti-inflammatory can prevent further damage. Objective: To determine the effect of giving turmeric extract (Curcuma longa) on the liver histopathological picture of male Sprague Dawley rats induced 7,12 Dimethylbenzene α anthracene (DMBA). Methods: This study used an experimental method with a post only control group design approach. The sample in this study consisted of 30 rats which were divided into 6 groups each consisting of 5 rats. The research data were tested with the Shapiro-Wilk normality test and continued with the non-parametric Kruskall Wallis test. Results: The kruskall wallis test obtained p value = 0.011 (p> 0.05) indicating a significant difference between the test groups, followed by the Mann Whitney test which showed insignificant differences for the DMBA and turmeric extract groups on the histopathological picture of the liver. However, there was a decrease in the rate of liver damage after giving turmeric Conclusion: There is a decrease in the average degree of liver damage induced by DMBA after giving turmeric extract but there is no significant difference. Keywords: DMBA, Turmeric Extract, Liver Histopathology.